IMPLEMENTASI CONTINUITY EDITING DALAM PRODUKSI VIDEO COMPANY PROFILE PT BOOGIE APPAREL INDONESIA - Bianka Dwinanda Larasati; Rici Tri Harpin Pranata (Jurnal Manajemen Pendidikan, 2026)
The development of digital media has prompted every company to use corporate profile videos as a medium for disseminating information that effectively conveys the company’s identity in an engaging manner. However, during the production of corporate profile videos, inconsistencies in transitions between shots are often encountered, which detracts from the visual experience for the audience. Therefore, this study aims to describe the production and editing process of PT Boogie Apparel Indonesia’s corporate profile video using continuity editing techniques. This study employs a descriptive qualitative method, with data collection conducted through literature review, observation, and interviews. The data analysis technique in this study is based on continuity editing principles, which include the 180-degree rule, shot-reverse shot, eyeline match, establishing shot, match on action, point of view, cut-in, and cutaway. This study concludes that the application of continuity editing techniques is capable of creating good visual continuity in every scene within the company profile video as a whole, so that transitions between shots appear more fluid and are easily understood by the audience. This study also found that the application of continuity editing techniques can be utilized by business-to-business companies while still projecting a professional image when introducing themselves through the presentation of company information in a more engaging manner.